Simultaneous Determination of Zn(II), Cd(II), Pb(II), and Cu(II) Using Differential Pulse Anodic Stripping Voltammetry at a Bismuth Film-Modified Electrode - Nguyen Mau Thanh; Nguyen Van Hop; Nguyen Dinh Luyen; Nguyen Hai Phong; Tran Thanh Tam Toan (Advances in Materials Science and Engineering)
The simultaneous electrochemical determination of Zn(II), Cd(II), Pb(II), and Cu(II) in the aqueous solution has been developed on the basis of the bismuth film glassy carbon electrode (GCE) using differential pulse anodic stripping voltammetry (DP-ASV). The bismuth film electrode (BiFE) was prepared by adding 500 ppb bismuth(III) directly to the sample solution and simultaneously depositing bismuth and the metal analytes on GCE. The optimal operational parameters, namely, accumulation potential (–1.6 V), accumulation time (110 s), pulsed amplitude (0.07 V), and scan rate (0.021 V·s−1), were found using a Box–Behnken design. Under the optimum conditions, a linear relationship exists between the current and the concentration of Zn(II), Cd(II), Pb(II), and Cu(II) in the range between 5.0 ppb and 110.0 ppb with the detection limits of 1.07 for Zn(II), 0.93 ppb for Cd(II), 0.65 ppb for Pb(II), and 0.94 ppb for Cu(II) calculated on the basis of a signal-to-noise ratio equal to 3 (S/N = 3). The interference experiments show that Co(II), Ni(II), and Fe(III) have a little influence on the DP-ASV signals of Zn(II), Cd(II), Pb(II), and Cu(II). In addition, a high reproducibility was indicated from small relative standard deviations (1.03%, 1.74%, 1.32%, and 4.74%) for 25 repeated measurements of 15 ppb copper, lead, cadmium, and zinc solutions. BiFE was successfully applied to determine Zn(II), Cd(II), Pb(II), and Cu(II) in river samples, and the results are in a good agreement with those determined with graphite furnace atomic absorption spectrometry (GF-AAS).